2014
DOI: 10.1093/cercor/bhu070
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Neurospecific Alternative Splicing Controls Neuronal Excitability in Mouse Models of Epilepsy

Abstract: Alternative splicing in the brain is dynamic and instrumental to adaptive changes in response to stimuli. Lysine-specific demethylase 1 (LSD1/KDM1A) is a ubiquitously expressed histone H3Lys4 demethylase that acts as a transcriptional co-repressor in complex with its molecular partners CoREST and HDAC1/2. In mammalian brain, alternative splicing of LSD1 mini-exon E8a gives rise to neuroLSD1, a neurospecific isoform that, upon phosphorylation, acts as a dominant-negative causing disassembly of the co-repressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…The generation of a mouse model lacking microexon E8a (neuroLSD1 KO mice) allowed us to characterize neuroLSD1 as an in vivo modulator of hippocampal excitability. We reported that shifts in the LSD1/neuroLSD1 ratio in response to activity contribute dynamically to the control of neuronal excitability by participating in the transcriptional mechanism of homeostatic adaptation (15). In this work we implicate LSD1 and neuroLSD1 in shaping emotional behavior as fine tuners of psychosocial stress-evoked transcription of IEGs.…”
mentioning
confidence: 67%
“…The generation of a mouse model lacking microexon E8a (neuroLSD1 KO mice) allowed us to characterize neuroLSD1 as an in vivo modulator of hippocampal excitability. We reported that shifts in the LSD1/neuroLSD1 ratio in response to activity contribute dynamically to the control of neuronal excitability by participating in the transcriptional mechanism of homeostatic adaptation (15). In this work we implicate LSD1 and neuroLSD1 in shaping emotional behavior as fine tuners of psychosocial stress-evoked transcription of IEGs.…”
mentioning
confidence: 67%
“…Previously, downregulation of RBFOX expression and misregulation of the RBFOX splicing regulatory network-comprising mostly longer alternative exons-were also observed in ASD patients (Voineagu et al, 2011;Weyn-Vanhentenryck et al, 2014). In addition, a recent study demonstrated that nSR100-and Nova1-mediated control of the inclusion of a 12-nt microexon in LSD1 (also known as KDM1A), a histone H3K4 demethylase, contributes to neuronal excitability in mice (Rusconi et al, 2014). This regulation was proposed to be important for susceptibility to seizure and could represent a molecular event that underlies epilepsy.…”
Section: Identification and Characterization Of A Highly Conserved Prmentioning
confidence: 97%
“…Furthermore, this altered pattern of inclusion in ASD subjects affects genes enriched in known genetic associations with ASD and is also highly correlated with reduced expression of nSR100 . Additional studies have linked microexon misregulation to schizophrenia and epilepsy (Ovadia and Shifman 2011;Rusconi et al 2014). In the future, it will be of considerable interest to address whether partial alteration of nSR100 levels in developing mice may contribute to phenotypes associated with human neurological disorders.…”
Section: Functional Impact Of Nsr100-regulated Microexonsmentioning
confidence: 99%